Prevalence, morphologic characteristic and predictors of organization of atrial auricle thrombi four weeks after anticoagulant preparation to scheduled electrical cardioversion of atrial fibrillation - Kalashnykova O.S. (Medičnì Perspektivi)
Goal: to study thrombosis prevalence and predictors of thrombi organization in atrial auricles in persistent non-valvular atrial fibrillation (NVAF) in patients undergoing transesophageal echocardiography (TEE) 4 weeks after oral anticoagulant therapy (OAC). Materials and methods: a total of 133 consecutive patients with NVAF, who underwent TЕE before electrical cardioversion (ECV) were included in the study. Results: The mean age of the participants was 60,3±0,9 years, 95 (71,4%) were men. The mean term of the last AF episode was 6,5±0,6 months. Duration of AF less than 1 year was in 47 (35,3%) patients, from 1 to 5 years – in у 61 (45,8%) patients, over 5 years – in 25 (18,8%) patients. 14 (10,5%) patients had underlying coronary artery disease (CAD), 84 (63,2%) patients had arterial hypertension, 31 (23,3%) had both CAD and arterial hypertension, 4 (3,0%) had cardiomyopathy, 80 (60,2%) were obese. NYHA I FC of heart failure (HF) was diagnozed in 8 (6,0%) patients, II FC – in 94 (70,7%) patients and III FC – in 31 (23,3%) patients. GFR > 90 ml/min/1,73m² was in 9 (6,8%) patients, in 74 (55,6%) it was decreased to 60-89 ml/min/1,73m², in 50 (37,6%) patients GFR was 30-59 ml/min/1,73m². In stratification of risk of thromboembolism complications (TEC) 91 (68,4%) fell into the high-risk group with the CHA2DS2-VASc score ≥ 2, 32 (24,1%) patients were in the moderate-risk group and 10 (7,5%) had CHA2DS2-VASc score 0. TEE was performed in all patients 4 weeks after effective OAC therapy. In 40 (37,6%) patients thrombi were detected in the left atrial auricle and in 26 (65,0%) patients they were organized. In 10 (7,5%) patients thrombis were detected in right atrial auricles and in 7 (70,0%) patients they were organized. In 63 (47,4%) patients thrombi were found in both atrial auricles and in 25 (39,7%) patients they were organized. Correlation was found between detection of non-organized thrombi, duration of AF less than 1 year and increase of total cholesterol. Thrombus organization was assotiated with AF duration more than 1 year. Conclusions: Clinical predictors linked with detection of non-organized atrial auricles thrombi in NVAF patients 4 weeks after OAC therapy are duration of AF less than 1 year, increase of total cholesterol, while thrombi organization is assotiated with AF duration more than 1 year.